Care providers' perspectives on disrespect and abuse of women during facility-based childbirth in Africa: a qualitative systematic review protocol. Issue 5 (May 2020) - Adinew, Yohannes Mehretie; Hall, Helen; Marshall, Amy; Kelly, Janet
ABSTRACT: Objective: The objective of this review is to identify and synthesize the best available qualitative evidence to understand healthcare providers' views on disrespect and abuse of women during facility-based childbirth in Africa. Introduction: Everyday, approximately 800 women die from preventable pregnancy- and childbirth-related causes worldwide; poorer women living in developing countries comprise 99% of these deaths. Maternal mortality has no single cause or solution, but the most effective preventive strategy is ensuring that every woman gives birth in an equipped health facility with the help of skilled providers. Yet, many women decline to attend facility-based delivery, often due to disrespect and abuse received during childbirth. Inclusion criteria: This systematic review will consider studies that include views of care providers regarding disrespect and abuse of women in birthing facilities, including verbal, physical and sexual abuse; stigma; discrimination; substandard care; neglect; and trust and communication problems. Qualitative studies that relate to Africa published in English from 1990 will be included. Methods: PubMed, CINAHL, Embase, Scopus, African Index Medicus and Web of Science, and selected gray literature sources, will be searched for eligible papers. Titles and abstracts of obtained documents will be assessed by the lead reviewer against the inclusion criteria. Identified documents will then be appraised for relevance and rigor by two independent reviewers. Data will be extracted by two independent reviewers and graded according to the ConQual approach.